The Impact of COVID-19 Pandemic in South African Correctional Centres: Challenges and Solutions - Patrick Bashizi Bashige Murhula (International Journal of Conflict and Violence, 2023)
The outbreak of COVID-19 was declared a public health emergency of international concern by the World Health Organization (WHO) on 30 January 2020. Many nations, including South Africa, have seen an increase in COVID-19 outbreaks in their population, including those working in and incarcerated in correctional centres. Responding to COVID-19 in correctional centres is a major challenge, particularly due to overcrowding and limited medical resources. This paper uses secondary data to investigate the spread of COVID-19 in South African correctional centres. It focuses on the problems faced by the South African Department of Correctional Services in preventing the spread of COVID-19 in its correctional facilities. The author proposes measures to be followed to prevent the spread of COVID-19 in such facilities. The findings reveal that despite efforts to prevent the spread of COVID-19 in South African correctional centres, the virus spread rapidly among inmates and prison workers.